Perancangan Sistem Informasi Aset Sekolah Berbasis Website Pada SMK N 5 Telkom Banda Aceh - Efan Maulana; Juniana Husna; Banta Cut (LPPM Universitas Internasional Batam, 2023)
SMK N 5 Telkom Banda Aceh is a vocational school, at the SMK the data collection for assets is very manual, that is, they still use the books that have been provided. When there are teachers or students who want to borrow assets, they have to meet the bookkeeper first and also in inputting staff reports. manually in excel. As a result, the staff who manage the goods will have difficulty and also when the book is lost, the staff will have even more difficulties. Therefore the aim of this study is to create a website-based school asset information system so that staff work is easier and more organized, this study uses the SDLC method so that it can produce an asset information system website as designed. The existence of this website makes it easier for staff in asset management in terms of managing asset data and makes it easier for teachers or students to borrow or return school assets.